Nitrate reductase from Spinacea oleracea. FAD and the reactivation of the enzyme treated with p-Hydroxymercuribenzoate (Revista Española de Fisiología, 1977)
Spinach nitrate reductase complex previously inactivated by treatment with mercurials p-hydroxymercuribenzoate or p-hydroxymercuriphenyl sulphonate can be reactivated by incubation with dithioerythritol. The reactivation of NADH-diaphorase seems to be FAD-dependent, whereas that of FNH2-nitrate reductase is not. The requirement of FAD for NADH-inactivation of nitrate reductase treated with p-hydroxymercuribenzoate disappears after treatment with dithioerythritol.